Facile synthesis of α-Fe2O3 nanodisk with superior photocatalytic performance and mechanism insight. Issue 1 (16th January 2015) - Huang, Yang; Ding, Dahu; Zhu, Minshen; Meng, Wenjun; Huang, Yan; Geng, Fengxia; Li, Jie; Lin, Jing; Tang, Chengchun; Lei, Zhongfang; Zhang, Zhenya; Zhi, Chunyi
Abstract: Intrinsic short hole diffusion length is a well-known problem for α -Fe2 O3 as a visible-light photocatalytic material. In this paper, a nanodisk morphology was designed to remarkably enhance separation of electron-hole pairs of α -Fe2 O3 . As expected, α -Fe2 O3 nanodisks presented superior photocatalytic activity toward methylene blue degradation: more than 90% of the dye could be photodegraded within 30 min in comparison with a degradation efficiency of 50% for conventional Fe2 O3 powder. The unique multilayer structure is thought to play a key role in the remarkably improved photocatalytic performance. Further experiments involving mechanism investigations revealed that instead of high surface area, ·OH plays a crucial role in methylene blue degradation and that O ·2− may also contribute effectively to the degradation process. This paper demonstrates a facile and energy-saving route to fabricating homogenous α -Fe2 O3 nanodisks with superior photocatalytic activity that is suitable for the treatment of contaminated water and that meets the requirement of mass production.